Analisis Orientasi Industri Guna Menghadapi Tantangan Industri (Studi Kasus: Pabrik Gula Kebon Agung, Malang) - Riswanda, Irene; Wirahayu, Yuswanti Ariani (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The sugar industry in Indonesia plays a key role in supporting national food needs as sugar consumption continues to rise. As one of the largest sugar factories in East Java, Kebon Agung Sugar Factory faces significant challenges. Therefore, this study aims to analyze the industrial orientation of Kebon Agung Sugar Factory in addressing challenges such as sugar price fluctuations, climate change, and sustainability demands. This study uses a descriptive qualitative method with data collected through literature studies. The research findings show that the factory’s location, close to sugarcane plantations, supports operational effectiveness, reduces logistics costs, and increases production efficiency. In terms of the market, the factory focuses on the domestic market, which has high sugar consumption, and applies product diversification strategies to expand market reach. In technology orientation, the factory adopts innovations such as modern machinery and environmentally friendly waste management practices.Social orientation is evident through partnerships with local farmers to ensure a stable and high-quality raw material supply, providing support like superior seedlings, production facilities, and training. Environmentally, the factory manages liquid waste, uses biomass for energy, and conducts environmental rehabilitation.This study concludes that an integrated industrial orientation approach can enhance competitiveness and operational sustainability for Kebon Agung Sugar Factory